The Relationship between Food Security and Gestational Diabetes among Pregnant Women - Shontreal Cooper; Maura Graham; Chia-Ling Kuo; Raminder Khangura; Adrienne Schmidt; Stephanie Bakaysa (Thieme Medical Publishers, Inc., 2022)
The objective were to: (1) evaluate associations between food security and women diagnosed with gestational diabetes mellitus (GDM) and (2) evaluate if women in food insecure (FI) households had adverse maternal and neonatal outcomes. This was an observational study from October 2018 until September 2019. Postpartum resident clinic patients who delivered term, singleton infant at 37 weeks' or longer gestation were screened. Participants completed a survey using the U.S. Household Food Security Survey Module (US HFSSM). Survey responses were classified as: food secure (FS) and FI (marginal, low, very low FS). The primary outcome was GDM. Our secondary outcome was neonatal intensive care unit (NICU) admissions for hypoglycemia. We evaluated the rate of GDM in FS and FI groups. Demographic data included: prepregnancy body mass index, total weight gain during pregnancy, birth weight, and mode of delivery. A logistic regression model was used to analyze the association between food insecurity and GDM. A p-value of less than 0.05 was considered statistically significant. There were 150 patients screened to participate; of these, 70 patients were enrolled (36 GDM and 34 without GDM [NGDM]). More patients in FI households, 71% (n = 17), were diagnosed with GDM, compared with 33% (n = 15) in the FS (FS) households (adjusted odds ratio 7.05; p < 0.01). Of patients who reported FI, 50% (n = 12) were black, 46% (n = 11) Hispanic, and 4% (n = 1) Caucasian, compared with 13% (n = 6) black, 30% (n = 14) Hispanic, and 57% (n = 26) Caucasian in patients who reported FS (p < 0.001). Although not significant, 25% (n = 6) of neonates from an FI household had an NICU admission for hypoglycemia compared with 7% (n = 3) from an FS household (p = 0.054). Pregnant women with GDM are more likely to experience FI than those with NGDM. Infants of mothers in FI households also had increased rates of NICU admission for hypoglycemia.